Application of Phrase Elements: “Owning, Receiving, Storing, Controlling without Rights and Against the Law in Article 112 and Article 114 of the Narcotics Law in Indonesia in ensnaring Narcotics Couriers - Ifahda Pratama Hapsari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Narcotics crime in Indonesia is a problem that until now has never ended. One of the problems is the increasing number of drug abusers. In our country, narcotics users / narcotics addicts can already be said to be criminals. In the Narcotics Law no. 35 of 2009 it is explained that what is meant by narcotics abusers are people who use narcotics without rights or against the law. 35 of 2009 concerning Narcotics. Narcotics crime is seen as a form of crime that has serious consequences for the future of this nation, especially the younger generation.There is an ambiguity problem in the Narcotics Law, and the problem is that Article 112 of the Narcotics Law Article 112 of the Narcotics Law contains the phrase "owning, storing, controlling" narcotics. Therefore, narcotics abusers are more appropriately charged with Article 127 of the Narcotics Law. The method used in this writing uses the normative method which examines the problems of legislation. Which aims to: and explore the application of the phrase Article and the meaning contained therein.